Identifying the sector bias of technical change - Thomas von Brasch (Statistics Norway, Research Department, 2015)
The empirical literature studying the sector bias of technical change has only focused on skill-biased technical change. In this paper, I analyse the sector bias of both factor-neutral and factor-biased technical change. In Norwegian data from 1972 to 2007 the empirical evidence is not clear on the impact of a sector bias of skill-biased technical change, but it points to a sector bias of factor-neutral technical change from the 1970s to the 1990s. That said, the impact of the sector bias seems to have reduced towards the latter part of the sample period. I also evaluate the cross-section model used in the literature and show the strong restrictions that must be placed on a vector equilibrium correction model to end up with the standard model. If these restrictions do not hold, the results reported in the literature may be biased. I show that the restrictions are strongly rejected, and that erroneously imposing them significantly changes the estimates of skill-biased technical change in many sectors. These results can, to some extent, be traced back to how the cross-section model ignores initial disequilibrium and imposes factors of production to be either complements or substitutes
Keywords: C5; J3; O3; 330; Econometric modeling; Technical change; Sector bias